2016
DOI: 10.1093/abbs/gmw022
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a metabolomics profile of arsenic trioxide effect in gastric carcinoma cell line SGC7901

Abstract: Arsenic trioxide (ATO) is highly effective for treating acute promyelocytic leukemia. It also holds the promise for treating solid tumors, including gastric carcinoma. However, the molecular mechanism of the effectiveness of ATO to solid tumor is still poorly understood. In this study, we chosed gastric carcinoma as an example and tried to reveal the antitumor mechanism through metabolomics. Gastric carcinoma cell line SGC7901 was treated with ATO for 6, 12, and 24 h. The global metabolite profiles were monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Furthermore, our data showed that NAMPT protein expression was dramatically decreased along with increasing ATO concentrations, suggesting that NAMPT inhibition might be involved in the mechanism of ATO-induced cancer cell death. Similar to this finding, a recent study showed that ATO greatly impacted several metabolomics pathways on gastric carcinoma cells, suggesting that these metabolomics changes could help elucidate the antitumor mechanism of ATO (21). Generally, NAMPT expression is positively regulated by various transcription factors, such as FoxO1 and NF-κB (22, 23).…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, our data showed that NAMPT protein expression was dramatically decreased along with increasing ATO concentrations, suggesting that NAMPT inhibition might be involved in the mechanism of ATO-induced cancer cell death. Similar to this finding, a recent study showed that ATO greatly impacted several metabolomics pathways on gastric carcinoma cells, suggesting that these metabolomics changes could help elucidate the antitumor mechanism of ATO (21). Generally, NAMPT expression is positively regulated by various transcription factors, such as FoxO1 and NF-κB (22, 23).…”
Section: Discussionsupporting
confidence: 76%
“…The UPLC/MS/MS platform was based on a Waters Acquity UPLC (Waters, Milford, MA, United States) and a linear trap quadrupole (LTQ) mass spectrometer (Thermo Fisher, Corporation), which had a linear ion-trap (LIT) front end and a Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometer backend. The extract samples were split into two aliquots, dried and then reconstituted in acidic or basic LC-compatible solvents, and each solvent contained 11 or more internal standards at fixed concentrations ( Chen et al, 2016 ). The acidic extract samples of one aliquot was analyzed for positive ions, while the other basic extract samples was analyzed for negative ions in two independent injections using separate acid/base dedicated 2.1 mm × 100 mm Waters BEH C18 1.7 μm particle columns heated to 40°C.…”
Section: Methodsmentioning
confidence: 99%
“…For UPLC/MS/MS platform, accurate mass determination could be performed for the ions with counts greater than two million and made on the parent ion as well as fragments for that the typical mass error less than 5 ppm. Peaks were identified using Metabolon’s proprietary peak integration in-house software, and component parts were stored in a separate and specifically designed complex data structure ( Chen et al, 2016 ). The one-way analysis of variance (ANOVA) was used to determine the significant differences between the means of tested groups.…”
Section: Methodsmentioning
confidence: 99%
“…Functional endpoints relevant to a response biomarker would include cell death or a reduction in cell proliferation. Unfortunately, most in-vitro studies on drug-induced changes in the metabolome primarily involve a description of changes in the metabolome that result from the drug itself, or it is unclear whether the changes are pharmacologic or due to impairment of tumor cell expansion [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Serial Monitoring Of the Metabolomementioning
confidence: 99%